UANG PANAI’: MENYOROTI PERGESERAN PARADIGMA MASYARAKAT KONTEMPORER PERSPEKTIF HUKUM ISLAM - Nurfadillah, Rizkyanti; Putri Ayu Ramadhani; Al Fitrah Maharanny (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
The Panai’ money tradition in Indonesia has experienced a shift in meaning and practice in the contemporary era. The increase in its value triggers financial burdens, delays in marriage, disputes between families, and exploitation of women. The phenomenon of "commercialization" of marriage reinforces the stereotype of women as an economic burden. This research aims to analyze the shift in the panai money paradigm from an Islamic legal perspective. The research method used is qualitative with an interdisciplinary approach, combining Islamic law, anthropology, sociology and economics. Data was collected through literature study and textual analysis of Islamic legal sources related to marriage and dowry. The research results show that the shift in the panai money paradigm is caused by social, economic and cultural factors. Islamic law offers a solution to overcome this paradigm shift by emphasizing justice, balance, and prohibiting the "commercialization" of marriage. Panai money should be a symbol of appreciation and commitment in building a harmonious household life.